1996
DOI: 10.1002/j.1550-8528.1996.tb00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Esteem and Change in Body Mass Index over 3 Years in a Cohort of Adolescents

Abstract: FRENCH, SIMONE A, CHERYL L PERRY, GLORIA R LEON AND JAYNE A FULKERSON. Self-esteem and change in body mass index over 3 years in a cohort of adolescents. ObesRes. 1996;4:27-33. Self-esteem has been hypothesized to be lower in obese adolescents relative to their normal weight peers and to be an important factor in preventing or reversing obesity. The present study examined the relationship between obesity and self-esteem crosssectionally and prospectively over three years in a cohort of 1278 adolescents in grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
8

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 36 publications
(42 reference statements)
2
53
0
8
Order By: Relevance
“…One study in black children (51) and one study in white adolescent females (20) suggest high self-esteem is protective against increases in body mass index over time. Additional studies are needed to examine self-esteem and body-esteem in relationship to age of onset of obesity, severity and duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in black children (51) and one study in white adolescent females (20) suggest high self-esteem is protective against increases in body mass index over time. Additional studies are needed to examine self-esteem and body-esteem in relationship to age of onset of obesity, severity and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Gortmaker et al (23) found no cross-sectional relationship between overweight status and self-esteem in 10,039 young adults aged 16 to 24. However, French et al (20) found an inverse relationship between body mass index and physical appearance self-esteem in 1278 white female and male adolescents. In addition, in females, body mass index was inversely related with global self-esteem, close friendship self-esteem and behavioral conduct self-esteem.…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…9 Until the mid-1990s the evidence on the relation between obesity and self-esteem in children was surprisingly inconsistent. 10 However, subsequent research has shown reduced global self-worth and reduced physical appearance selfesteem in obese adolescents, 11 obese preadolescents, [12][13][14] and overweight 5 year olds. 15 Low self-esteem is important because it is a risk factor for negative affective states such as anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…37 Feelings of low self-worth, especially in relation to physical appearance, are found in some, but not all, overweight children and adolescents. 38,39 It has been observed that food advertisements use emotional appeals, linking products with concepts such as fun, happiness, health and wellbeing, and so marketing personal enhancement. 40,41 The strength and immediacy of emotional appeals, coupled with low body esteem, may make overweight children particularly vulnerable to commercials that promote personal enhancement via the consumption of foods.…”
Section: Introductionmentioning
confidence: 99%